Wild animals housed at the IBAMA triage center in Southern Brazil, 2005–2021: a glimpse into the endless conflicts between man and other animals. - Farias Cruz, Cláudio Estêvão; Silva Sores, Camila Eloine; Bonamigo Hirt, Gustavo; Carniel Wagner, Paulo Guilherme; Andretta, Inês; Nisa-Castro Neto, Walter (Ethnobiology and Conservation, 2022)
Spurred on by the illegal billion-dollar revenue, the capture and trade of wild fauna remain the leading illegal activities in Brazil, and elsewhere. We present and discuss insights into the wild animals housed at the Wild Animal Triage Center in Southern Brazil. Recorded data from 2005 to 2021 were used. A total of 36,950 animals were sheltered in that period, and most of them were common passerines (24.182) such as the Saffron Finch, and Red-crested Cardinal, among many others confiscated after inspections or reports. Passerines have long been the top trafficked species in Brazil and abroad, where birdkeeping has strong cultural and economic values. The totals per class were 29,784 birds, 2,584 insects, 2,237 reptiles, and 2,170 mammals. Since they were mostly relinquished by the population rather than seized, most mammals, insects, and reptiles were probably unwanted guests in human spaces, tendency that illustrates the human difficulty in coexisting with wildlife. A total of 3,085 animals exhibited some threat or risk of extinction, which, as a general rule, grants them conservation priority. However, regardless of class, most animals (31,142) in this study were rated as least concern on the red lists, a trend in wildlife trafficking linked to the category criteria of being widely distributed species with abundant populations, and often, in close contact with human neighbors. Maintaining an abundance of common and nonthreatened species can be justified by the greater extent of their ecosystem services, from a local to global scale. Our results further highlight the urgent need to change our ways of interacting with wildlife.